Corporate social responsibility and dividend policy: a strategic choice in family firms. Issue 2 (4th January 2021) - Sheikh, Muhammad Fayyaz; Bhutta, Aamir Inam; Rehman, Bareera; Bazil, Muhammad; Hassan, Ali
Abstract : Purpose: The purpose of this study is to examine whether corporate social responsibility (CSR) affects dividend policy (the propensity to pay dividends as well as the dividend payout ratio) and what role family ownership plays in this regard in an emerging market. Design/methodology/approach: The study uses a sample of 1, 480 observations from Pakistan for the period 2010–2016 and accounts for Hackman self-selection bias and endogeneity issues using a robust regression analysis. CSR activity is measured by CSR score developed through a content analysis of firms' annual reports. Findings: The study finds that the greater number of CSR activities increases the propensity to pay dividends, but reduces the dividend payout in dividend-paying firms. On the other hand, in family firms, the greater number CSR activities decreases the propensity to pay dividends, but increases the dividend payout in dividend-paying firms. The findings hold for a series of robustness and sensitivity checks, for example, alternative measures, specifications and estimators. Practical implications: A trade-off between firms' CSR activities and dividend policy needs to be the point of concern for investors, minority shareholders and policy makers. The role of the non-executive and independent directors becomes more important, especially in the family firms where family members sitting on the boards may drive CSR activities in their own interests opportunistically. The potential opportunistic behaviour of family members warrants the need for policy reform initiatives to strengthen the protection of other stakeholders' interests. Originality/value: The study highlights that family owners' efforts to preserve their socio-emotional wealth in family firms affect the relationship between CSR activities and dividend policy. Further, the relationship between CSR and dividend policy in emerging markets is different from developed markets. This study simultaneously focuses on both the propensity to pay dividends and the amount of dividend payment and documents that the implications of CSR are different for them.